Biomaterial-based regenerative therapeutic strategies for spinal cord injury - Keyi Chen; Wei Yu; Genjiang Zheng; Zeng Xu; Chen Yang; Yunhao Wang; Zhihao Yue; Weien Yuan; Bo Hu; Huajiang Chen (NPG Asia Materials)
Abstract As one of the most intractable neurological diseases, spinal cord injury (SCI) often leads to permanent neurological impairment in patients. Unfortunately, due to the complex pathological mechanisms and unique postinjury microenvironment, there is currently no way to completely repair the injured spinal cord. In recent years, with the rapid development of tissue engineering technology, the combination of biomaterials and medicine has provided a new idea for treating SCI. Here, we systematically summarize representative biomaterials, including natural, synthetic, nano, and hybrid materials, and their applications in SCI treatment. In addition, we describe several state-of-the-art fabrication techniques for tissue engineering. Importantly, we provide novel insights for the use of biomaterial-based therapeutic strategies to reduce secondary damage and promote repair. Finally, we discuss several biomaterial clinical studies. This review aims to provide a reference and new insights for the future exploration of spinal cord regeneration strategies.